Milk compositions of dairy goats with and without subclinical intrammary infections - Abd Razak, Iffah Nadzirah (2015)
Intramammary infections (IMI) affect the composition of milk thus lowering the hygienic value and quality of the milk. This study was carried out to compare milk composition parameters of dairy goats with and without the subclinical IMI, to determine the effect of subclinical IMI on the milk composition and also to determine the relationship of somatic cell count (SCC) on the milk compositions. A total 20 Saanen goats from one of Ladang Angkat of Faculty of Veterinary Medicine, University of Putra Malaysia (FPV,UPM) was involved in this study and Carlifonia Matitis Test (CMT) was used to identify subclinically infected and uninfected does. The milk composition parameters such as fat , protein, casein, lactose, total solid, solid non fat, acidity, free fatty acid were analysed using FOSS MilkoscanTM FT2. However, no significant difference(p>0.05) was found for all the milk composition parameteres between subclinically intramammary infected does with the uninfected does, however, a significant difference (p<0.05) of the SCC between subclinically infected and uninfected of dairy goats at Ladang Angkat FPV, UPM was found. In addition, the correlation coefficient between SCC and all the milk composition parameters was found to be low( R<0.5).These results differ from other previous studies that showed significant changes in the milk composition during subclinical mastitis and strong correlation between SCC and milk composition parameters.It can be concluded that no significant different of milk composition of subclinically infected and uninfected does, no correlation between SCC and milk composition and no effect of subclinical mastitis on the milk composition thus none of the milk composition parameter is suitable to indicates subclinical IMI.